Pengaruh Citra Perusahaan dan Kualitas Layanan terhadap Loyalitas dengan Kepercayaan sebagai Variabel Mediasi - Madyaratri, Dellafany Noor; Andjarwati, Anik Lestari (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This paper aimed to study the effect of corporate image and service quality on loyalty by using trust as a mediating variable. This research uses quantitative data. The sampling technique used was non-probability sampling with the type of judgmental sampling). The sample used in this study were 220 respondents. The research method used path analysis–data collection through a questionnaire. The results showed that company image has a positive and significant effect on loyalty, service quality has a positive and significant effect on loyalty, the corporate image has a positive and significant effect on trust, service quality has a positive and significant effect on trust, and trust has a positive and significant effect on loyalty. Kantor Pos Trenggalek is expected to improve the image of Kantor Pos Trenggalek so that customer perception will be better for the services provided and improve and develop the quality of services provided to customers and fix service problems.